Curcuma amada roxb-chemical composition of rhizome oil - Singh, Gurdip (2003)
GC and GC-MS analysis showed the presence of twenty two components accounting for 91.47% of the rhizome oil from Curcuma amada. Major constituent is myrcene (80.54%) followed by beta-pinene (4.64%), (E)-beta-ocimene (1.885) and perillene (1.47%).